Development STEM-Based Biotechnology Learning Tools to Practice Critical Thinking - Ayu Widiarti; Muslimin Ibrahim; Yuliani Yuliani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study aims to describe the validity of learning tools in terms of several aspects such as content, language, and presentation. The method used in this research is to use a modified 4D (Define, Design, and Development), model and implemented in the Postgraduate Program for Science Education, State University of Surabaya. The data collection technique was carried out by the validation method. The assessment instrument uses a validation sheet. The tools developed are in the form of lesson plans, Student worksheet, and critical thinking ability tests. The validity of this STEM-based biotechnology learning tool is based on content feasibility, language feasibility, and presentation feasibility. Validity of STEM-based biotechnology learning tools were assessed by three validators consisting of two biology lecturers and one biology teacher. Data analysis was carried out quantitatively. The results of the validation of STEM-based biotechnology learning devices by three validators obtained an average score of 3.83 lesson plans, 3.67 Student worksheet, and 3.67 critical thinking ability test with a very valid category. Based on data analysis, it can be concluded that the learning tools developed are valid and suitable for use in learning